Estratégias competitivas para empresas turísticas: um estudo no setor hoteleiro de um município do litoral catarinense - Gohr, Cláudia Fabiana (2010)
The theme of strategies has been a subject that is increasingly in evidence in organizational studies. Tourism research has not been different, although much of the literature present studies related to strategies aimed at developing tourism destinations. The objective of this article is to identify strategies adopted by the hotel sector in a Brazilian coastal city with an elevated tourism flow. The research was characterized as a descriptive case study. The techniques of data collection were the semi-structured interview, the passive observation and the document analysis. The research concluded that the sector uses various types of competitive strategies and these reflect the own structure of the sector.